Simulation of the influence of constant uniform magnetic field on a miniature LIT mass spectrometer. Issue 2 (April 2018) - Feng, Yan; Pei, Xiaoqiang; Cheng, Yongjun; Sun, Wenjun; Li, Gang; Wang, Yongjun; Xi, Zhenhua; Zhang, Huzhong
In this paper, the effects of constant uniform magnetic fields on a miniature linear ion trap mass spectrometer with hyperbolic electrodes are simulated using SIMION 8.0 3D software. Magnetic fields in different directions have different effects on the trajectories of the trapped ions and the shape of the ion cloud. When the magnetic field is applied in the z-direction, namely the ion injection direction, the magnetic field will cause the ions focusing to the z-axis, and exert a compression effect on the ion cloud. When the magnetic field is applied in the x-y plane, the original ion cloud will be expanded due to the action of the applied magnetic field, and the ion cloud plane after expansion is always perpendicular to the direction of the magnetic field. The discovery of influence field of magnetic will bring some useful inspiration for the improvement of ion trapping efficiency, mass resolution, sensitivity and trapping capacity, which is conductive to the performance enhancement utilization of magnetic field, even in the industrial application development and other aspects.